SDQ: discriminative validity and diagnostic potential - Silva, Thaysa B. F.; Osório, Flávia L.; Loureiro, Sonia R. (Frontiers in Psychology, 2015)
The Strengths and Difficulties Questionnaire (SDQ) was designed to screen for behavioral problems in youths based on cutoff points that favor the instrument’s diagnostic sensitivity. The present study aimed to analyze the discriminative validity of the SDQ to identify behavioral difficulties and prosocial resources in school-age children compared with the diagnostic data collected by the corresponding sections of the Development and Well-being Assessment (DAWBA). In addition, new cutoff points that value specificity were defined for the SDQ scales, exploring its diagnostic potential. This study was conducted in Brazil and assessed a community convenience sample that consisted of 120 children aged 6 to 12 years who were not under psychological/psychiatric treatment. The mothers of the participants also completed a sociodemographic questionnaire. Descriptive statistics were used to clinically characterize the sample. A ROC curve was used to assess the discriminant validity of the SDQ, and new cutoff points were established to maximize the instrument’s specificity. The new cutoff points enabled a significant increase in specificity without a significant loss of sensitivity, which favors approaches based on measures of screening and diagnosis yet does not damage the instrument’s screening capacity. The following increases were observed: 100% for the depressive disorder scale (cutoff point=7), 95.1% for the generalized anxiety disorder scale (cutoff point=7), 46.6% for the conduct disorder scale (cutoff point=6), 19.2% for the hyperactive disorder scale (cutoff point=8), and 27.6% for the antisocial personality disorder scale (cutoff point=6). A cutoff point of 8 was applied to the prosocial behavior scale, which exhibited a 62.1% increase in specificity. The use of more specific cutoff points generated more accurate results and favored SDQ's use, particularly in contexts of care that require more precise and faster procedures for identification of problems.